How the smart product attributes influence consumer adoption intention - Li, Ming; Bai, Xuchen; Xing, Saipeng; Wang, Xueying (Frontiers in Psychology, 2023)
Compared with traditional products, the connection attributes and intelligence attributes of the smart product are their differentiated competitive advantages. In order to understand how smart product attributes affect consumer attitudes and the influencing mechanism, we carry out this study. In the framework of psychological empowerment, this paper explores the relationship between smart product attributes and consumers’ adoption intention. We consider that companies can launch a range of smart products, where the probability of success is related to the degree to which intelligent and connection attributes stimulate consumer motivation. Smart products with intelligence attributes and connection attributes can improve consumers’ cognition of the four motivations consist of meaning, ability, autonomy and influence, which activate consumers’ psychological sense of empowerment, and thus improve consumers’ willingness to adopt. In addition, we also find that consumer heterogeneity influences this process. This paper mainly reports the moderating effect of Consumer domain-specific innovation. We find that the connection and intelligence attributes of smart products stimulate consumers’ adoption intention effectively. The findings of this paper complement innovation management literature related to smart product attributes and provide suggestions for enterprises to introduce smart products.